Analisis Penggunaan Media Sosial untuk Pencarian Informasi dan Media Komunikasi Menggunakan Model Uses and Gratification - Rispa Rianti Damanik; Johan Jimmy Carter Tambotoh (STMIK Budi Darma, 2022)
The use of social media continues to increase for various purposes, such as information seeking and communication media. This is because social media makes it easier for users to interact, communicate without thinking about distance, and seek information. This study aims to measure and analyze the use of social media as a search for infor mation and communication media for its users. This study uses the Uses and Gratification model and analyzed using the Structural Equation Modeling method. From the results of collecting and processing data from 263 respondents, it was found that there were 6 accepted hypotheses, namely Hypothesis 1, information seeking influences communication media because this is indicated by the T-Statistics value of 2.724. Hypothesis 2 is accepted with the results of T-Statistics 4.457, this shows that socializing affects communication media. Then, Hypothesis 4 is accepted with a T-Statistics value of 3.197, namely status seeking positively influences the use of social media. Hypothesis 5 is accepted with the conclusion that socializing positively affects the use of social media. Hypothesis 5 is accepted, so it can be said that entertainment affects the use of social media. However, one hypothesis is rejected, namely Hypothesis 3 so that information seeking does not affect the use of social media